Use of levothyroxine among pregnant women with subclinical hypothyroidism in the United Kingdom: A population‐based assessment - Ya‐Hui Yu; Kristian B. Filion; Pauline Reynier; Robert W. Platt; Oriana H. Y. Yu; Sonia M. Grandi (Wiley, 2021)
Abstract Our study aimed to describe levothyroxine prescription patterns and trends over time among pregnant women with subclinical hypothyroidism (SCH) in the United Kingdom. We used data from the Clinical Practice Research Datalink linked to its Pregnancy Register and the Hospital Episode Statistics database from 1998 to 2017. The study population included women with a diagnosis of SCH or an abnormal thyroid‐simulated hormone (TSH) level one year prior to or during pregnancy. We compared characteristics between women who received a prescription for levothyroxine during pregnancy and those who did not. We further described the timing, dose, duration, and temporal trends of levothyroxine prescriptions. Our cohort included 6,757 pregnancies from 6,287 women with SCH, of whom 10% received levothyroxine during pregnancy. Among women who received levothyroxine, most received their first prescription during the first trimester (median gestational age: 7 weeks; interquartile range [IQR]: 0, 16) with a median daily dosage of 50 mcg (IQR: 50, 73). Levothyroxine prescription varied over time, decreasing from 23% of pregnant women in 1998 to 7.5% in 2003, remaining stable until 2014, and increasing to 12.5% in 2016. Smoking, diabetes, polycystic ovary syndrome, infertility, timing of SCH diagnosis, age, TSH level at diagnosis, and general practice regions were associated with prescription. Few women with SCH received levothyroxine during pregnancy, and treatment varied by patient characteristics and geographical regions. These results highlight the need to increase awareness among healthcare providers and will guide future studies that explore barriers to initiating levothyroxine treatment for women with SCH during pregnancy.